Pembinaan Pemasaran Digital dan Peningkatan Kualitas Laporan Keuangan pada Umkm Rafflesia di Kota Batam - Dian Efriyenty; Hikmah Hikmah; Khadijah Khadijah (ABDI SABHA (Jurnal Pengabdian kepada Masyarakat), 2021)
Implementation of community service activities carried out in the form of Digital Marketing Development and Quality Improvement of Financial Report on Rafflesia Small And Medium Enterprises in Batam City. Based on the results of the interview in the field that Rafflesia SMEs have problems marketing the results of production and financial recording. One form of marketing that is often used is only done bidding through relatives of SME members, Bazar and through exhibitions organized by the Cooperative Office and MSMEs. In general, SME members have limitations in mastering the use of information technology facilities with marketing media that is not known to the public. The training method used is to provide training on cases of SME transactions that need to be completed from journals to financial statements accompanied by training using digital marketing through social media. The methods used in the construction of Rafflesia SMEs to be given are survey methods, lecture methods, discussion methods and training methods. Devotion has been carried out 5 times with material making financial statements and digital marketing management through shopee. Rafflesia Small and Medium Enterprises (SMEs) that have been built in digital development, need to conduct exercises independently in the daily practice of SME mothers in terms of doing product promotion media to increase sales. So that it can get used to its daily business needs. Small and Medium Enterprises (SMEs) that have been built can prepare financial statements independently, so that Rafflesia SMEs are able to compile sak-etap standard financial statements.